Effects of Wrist Cooling on Recovery From Exercise-Induced Heat Stress With Firefighting Personal Protective Equipment. Issue 11 (November 2018) - Schlicht, Emily; Caruso, Ronald; Denby, Kelsey; Matias, Alexs; Dudar, Monique; Ives, Stephen J.
Abstract : Objective: To determine the effects of wrist cooling on recovery from exercise-induced heat stress (EIHS) from wearing firefighting personal protective equipment (PPE) and self-contained breathing apparatus. Methods: Using a single-blind, counterbalanced, crossover-design, in 11 healthy men, we measured heart rate (HR), HR variability (HRV), core temperature ( T Core ), thermal strain (TS), and fatigue at rest, during 30-minute of exercise in PPE+SCBA, and during recovery while wearing a wrist cooling band (control[off] vs cool[on]). Results: No differences were observed between trials at baseline or during exercise, in HR, T Core, TS, or fatigue. Time to 50% and recovery were not different between trials. Upon recovery, T Core was lower, while HR, fatigue, HRV, and TS were relatively indifferent with cooling. Conclusion: Wrist cooling after EIHS only modestly enhanced recovery, questioning its implementation during on-scene rehabilitation of firefighters.